2016
DOI: 10.1016/j.tem.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein L1 and Kidney Disease in African Americans

Abstract: Genetic variants in the Apolipoprotein L1 (APOL1) gene cause high rates of kidney disease in African Americans. These variants, found only in individuals with recent African ancestry, confer enhanced innate immunity against African trypanosomes. Though they are among the most powerful disease-causing common variants discovered to date, we are just beginning to understand how they promote kidney injury. Since APOL1 is only present in a few primate species, much of our current knowledge has come from natural exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 82 publications
(138 reference statements)
1
66
0
Order By: Relevance
“…6) 3134 . This rationale is supported by the fact that the APOL1 gene encodes a signal peptide sequence that targets newly synthesized protein for secretion, by the fact that exogenously added APOL1 risk-variant proteins, but not the non-risk-variant, affected endocytic machinery within podocytes (formation of autophagosomes)—the mechanism through which APOL1 risk proteins lyse trypanosomes 29 —and lastly, by studies describing suPAR–β 3 integrin-dependent endocytosis of hantaviruses 35,36 . Interestingly, a previous study showed that podocyte-specific expression of APOL1 risk variants in mice resulted in moderate podocyte depletion later in life and occasional preeclampsia 9 .…”
Section: Discussionmentioning
confidence: 99%
“…6) 3134 . This rationale is supported by the fact that the APOL1 gene encodes a signal peptide sequence that targets newly synthesized protein for secretion, by the fact that exogenously added APOL1 risk-variant proteins, but not the non-risk-variant, affected endocytic machinery within podocytes (formation of autophagosomes)—the mechanism through which APOL1 risk proteins lyse trypanosomes 29 —and lastly, by studies describing suPAR–β 3 integrin-dependent endocytosis of hantaviruses 35,36 . Interestingly, a previous study showed that podocyte-specific expression of APOL1 risk variants in mice resulted in moderate podocyte depletion later in life and occasional preeclampsia 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the role of circulating APOL1 was recognized as a trypanolytic factor . Until a decade ago, the role of the expressed protein in general, and in kidney cells in particular, was not appreciated . During the current decade, APOL1 mutants (G1 and G2) have been reported for their association with a higher incidence of chronic kidney disease in patients with African ancestry and considered to be renal risk variants (RRVs).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] APOL1 is the serum trypanosome lytic factor. 7 A high frequency of two APOL1 risk alleles associated with renal diseases in persons of African ancestry [8][9][10] is attributed to the evolution of trypanosome resistance to an ancestral G0 allele, whereas G1 and G2 variant riskassociated alleles confer pathogen resistance.…”
mentioning
confidence: 99%